A ANALISA PENGULANGAN (REPEAT) RADIOGRAF DI UNIT RADIOLOGI RUMAH SAKIT UMUM DAERAH MOHAMMAD NATSIR SOLOK: ANALISA PENGULANGAN (REPEAT)RADIOGRAF DI UNIT RADIOLOGI RUMAH SAKIT UMUM DAERAH MOHAMMAD NATSIR SOLOK - CICILLIA - ARTITIN (JURNAL TERAS KESEHATAN, 2022)
Repeat analysis is a systematic process on rejected catalog images and determines the type of repetition so as to minimize errors or repetitions that occur. Based on field observations from august to October 2020, the results were obtained with a percentage of 2.96%. therefore, it is necessary to have a repeat analysis program to determine the magnitude of the repetition rate and the factors causing the repetition to occur clearly. The type of research used is quantitative, carried out at the Radiology Unit of the Mohammad Natsir Solok Regional Hospital from January to march 2021. The data are grouped based on the repetition factor and calculated then processed using a formula that will be compared with the tolerance limit that has been set. The results of the study stated that the repetition of radiographs in January was 2.16% February was 2.81% and march 3.59%. then averaged to get a 2.80% result, while based on Permenkers No. 129 Of 2008 radiographic repetitions should not exceed 2%. The factor that causes repeat radiographs are patients' movement factor 9,7%, patient position factor 63.9% exposure factor 9.7%, equipment factor 4.2%, and artifact factor 12,5%.   Keywords: Repeat, Causative Factors, Computed Radiograf.